Gyrinus aquiris LeConte 1868 - Majka, Christopher (Zenodo, 2008)
Gyrinus aquiris LeConte, 1868 This species was reported from Prince Edward Island by Roughley (1991a), however, there are no voucher specimens from PEI in any collection consulted, nor was the species listed from the province by Fall (1922) or Oygur and Wolfe (1991). Consequently this species is removed from the faunal list of Prince Edward Island. : Published as part of Majka, Christopher, 2008, The aquatic Coleoptera of Prince Edward Island, Canada: new records and faunal composition, pp. 239-260 in ZooKeys 2 (2) on page 246, DOI: 10.3897/zookeys.2.25, http://zenodo.org/record/576401 : {"references": ["Roughley RE (1991 a) Family Haliplidae: crawling water beetles. In: Bousquet Y (Ed) Checklist of Beetles of Canada and Alaska. Agriculture Canada Publication 1861 / E: 60 - 61.", "Fall HC (1922) Th e North American species of Gyrinus (Coleoptera). Transactions of the American Entomological Society 47: 269 - 306.", "Oygur S, Wolfe GW (1991) Classification, distribution, and phylogeny of North American (north of Mexico) species of Gyrinus Muller Coleoptera: Gyrinidae. Bulletin of the American Museum of Natural History 207: 1 - 97."]}